Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Dengan Strategi Sumber Daya Manusia Sebagai Variabel Intervening : Studi Pada Pegawai Rektorat Universitas Palangka Raya - Suwandy Suwandy; Yunikewaty Yunikewaty; Achmad Syamsudin (Edunomics Journal, 2023)
This study aims to analyze the effect of leadership style on employee performance through HR strategy as an intervening variable. The method used in this research is explanatory research. The sample of this research is 63 people. Data were analyzed using descriptive analysis and inferential statistical analysis using the Structural Equation Modeling (SEM) model using the Partial Least Squares (SEM-PLS) approach. The results of the study concluded that leadership style does not directly affect employee performance, but through HR strategy, leadership style influences employee performance. In this connection HR strategy is a full mediation variable. The implications of this research illustrate that transformational leadership styles are more effective in developing HR strategies within the Rectorate of Palangka Raya University.